Abbau der kalten Progression: Nüchterne Analyse geboten - Katja Rietzler; Dieter Teichmann; Achim Truger (Wirtschaftsdienst, 2014)
Die Forderung nach einem Abbau der sogenannten kalten Progression im Einkommensteuertarif ist zu einem Dauerbrenner in der steuer- und finanzpolitischen Reformdebatte geworden. Doch womit wird diese Forderung eigentlich begründet? Welche Belastungen gehen tatsächlich von der kalten Progression aus? Wie haben sie sich im Zeitablauf entwickelt und wie sind sie verteilt? Besteht tatsächlich ein akuter Entlastungsbedarf? Nach einer eingehenden Analyse melden die Autoren daran erhebliche Zweifel an. – – The call for indexing the German income tax schedule to inflation in order to eliminate bracket creep has become widespread in the German tax policy debate. While it is indeed problematic that tax rates rise even when real incomes remain constant, the authors show that currently this is no reason for tax cuts. Changes in both the tax schedule and deductible allowances have more than offset the effects of bracket creep for most taxpayers since 1991. This is illustrated with calculations for a range of constant real incomes and family constellations. However, as the relative tax relief since 1991 has strongly favoured top incomes, a reform of the tax schedule that raises the top tax rate while providing some tax relief for lower and medium incomes may be justified.
Keywords: H11; H24; K34; 330; Steuergerechtigkeit; Steuerprogression; Steuerreform; Inflationsrate; Steuerinzidenz; Deutschland